Asuhan Keperawatan Pada Keluarga Tn. I Dengan Gangguan Sistem Kardiovaskuler: Hipertensi Pada Ny.S Di Desa Kebon Baru Kartasura - Rahmawati, Rahmawati; , H.M. Abi Muhlisin, SKM., M.Kep (2015)
NURSING CARE OF MR.I FAMILY WITH CARDIOVASCULAR SYSTEM DISORDERS: HYPERTENSION OF MRS.S IN KEBON BARU VILLAGE, KARTASURA (Rahmawati, 2015, 75 pages) ABSTRACT Background: Hypertension is a common health problem in the community. Some of the factors that can lead to hypertension are lifestyle, age, education and descent. Patients with hypertension in Kartasura area from January 2015 to April 2015 reached 1,016 people. Hypertension was ranked first in Kartasura. Objective: To determine the nursing care in family members with hypertension include assessment, intervention, implementation and nursing evaluation. Results: After nursing care for 3x30 minutes visitations, it is obtained that family are able to recognize the problem of hypertension, take the right decisions, able to perform progressive relaxation techniques and make traditional medicines for hypertension, modify the environment and also utilize the health care. Conclusion: Cooperation between the family and health care team is indispensable for the success of nursing care, therapeutic communication can encourage a more cooperative family. It can solve the nursing problem of acute pain related to family's inability in taking care of family member with hypertension and repetitive recurrence risk is related to the family's inability in recognizing the problem of hypertension. Keywords: hypertension, pain, repetitive recurrence risk